Investigation of anxiety levels and associated factor analysis in breast cancer patients undergoing chemotherapy with implanted venous access ports during the stable phase of disease - Min Wen; Yaling Zeng; Purong Zhang; Jing Yang; Zhenjun Zhang; Baisen Li; Zhiyan Chen; Chunyan Fan; Qiao Zhang; Gui Yang; Li Wen (PLoS ONE, 2025)
Aims To analyze the occurrence of anxiety and its influencing factors in stable stage breast cancer patients after chemotherapy with Implanted Venous Access Port (IVAP). Methods A total of 776 female breast cancer patients who underwent IVAP and completed chemotherapy in a tertiary cancer hospital from February 2019 to December 2021 were selected as the study subjects. General condition survey scale, sociological data, disease data, infusion port situation, and SAS anxiety scale were used for investigation to assess their anxiety status. Factors with statistically significant differences in univariate analysis were used as independent variables, and anxiety scale scores were used as dependent variables for multiple linear regression analysis of anxiety-related factors. Results Among the 776 stable stage breast cancer patients after chemotherapy with IVAP, the average score of the anxiety scale was 50.35 ± 10.93, and the prevalence of anxiety was 58.51%, including 312 (40.21%) mild anxiety patients, 124 (15.98%) moderate anxiety patients, and 18 (2.32%) severe anxiety patients. The results of multivariate analysis showed that physical condition, wound dehiscence, pulling sensation, foreign body sensation, and the use of other venous channels and the order of chemotherapy and surgery were influencing factors of anxiety in stable stage breast cancer patients after implantable venous port chemotherapy (P < 0.05). Conclusions Anxiety is common in stable stage breast cancer patients after chemotherapy with IVAP. Healthcare professionals need to pay attention to patients’ psychological problems, strengthen psychological assessment, standardize and refine infusion port management, and promote patients’ physical and psychological recovery.